Physical and anatomical features of rubber wood from three cultivars - Gilchrist K F; Gnanaharan R; McConchie D L (Indian Journal of Natural Rubber Research, 1997)
Rubber wood from three cultivars (GI 1, MK 3/2 and GG 2) of Hevea brasiliensis from plantations in southern Kerala, India, established in 1963 was evaluated for physical and anatomical properties. Results from this preliminary study indicate that there are possible differences among cultivars in basic density and tension wood.
Keywords: Density; Density; Fibre length; Fibre length; Hevea brasiliensis; Hevea brasiliensis; Rubber wood; Rubber wood; Shrinkage; Shrinkage; Tension wood; Tension wood